Weibliche Herrschaft im 18. Jahrhundert : Maria Theresia und Katharina die Große - Braun, Bettina; Kusber, Jan; Schnettger, Matthias (transcript-Verlag, 2020)
In Maria Theresa and Catherine the Great, the volume compares two of the most important rulers of the 18th century and shows how they met the special challenges they faced as ruling women.
Keywords: Maria Theresa, -- Empress of Austria, -- 1717-1780.; Catherine -- II, -- Empress of Russia, -- 1729-1796.; Catherine -- II, -- Empress of Russia, -- 1729-1796; Maria Theresa, -- Empress of Austria, -- 1717-1780; Empresses -- 18th century.; Aufklärung.; Biografievergleich.; Biography Comparison.; Catherine the Great.; Cultural History.; Enlightenment.; Female Rule.; Gender History.; Gender Studies.; Gender.; Geschichtswissenschaft.; Geschlecht.; Geschlechtergeschichte.; Herrschaft von Frauen.; History.; Katharina die Große.; Kulturgeschichte.; Monarchie.; Monarchy.; Impératrices -- 18e siècle.; HISTORY / Social History.; Empresses; 1700-1799; Electronic books.